Evaluation of methadone concentrations in bitches and in umbilical cords after epidural or systemic administration for caesarean section: A randomized trial. (May 2019) - Romagnoli, Noemi; Barbarossa, Andrea; Cunto, Marco; Ballotta, Giulia; Zambelli, Daniele; Armorini, Sara; Zaghini, Anna; Lambertini, Carlotta
Abstract: Objective: To measure plasma methadone concentrations in bitches and the umbilical cords of their puppies after systemic or epidural administration. Study design: Prospective, randomized, clinical study. Animals: A total of 27 healthy pregnant female dogs undergoing caesarean section, 4.3 ± 2.3 years of age and weighing 19.9 ± 13.2 kg. Methods: The dogs were randomly divided into three groups: 1) intramuscular methadone (0.3 mg kg –1 ) (group MET; n  = 9); 2) epidural methadone (0.1 mg kg –1 ) (group METEPI; n  = 9); and 3) epidural lidocaine (4.4 mg kg –1 ) [group CON (control group); n  = 9]. Ten minutes before induction, methadone was administered intramuscularly to the group MET dogs. Anaesthesia was induced with propofol and maintained with isoflurane. Cardiovascular and respiratory parameters were monitored throughout the anaesthesia. After induction, epidural anaesthesia was administered to dogs in groups METEPI and CON. Before any treatment (T0) and, as soon as the last foetus was removed from the uterus (T1), venous blood samples were collected from each dog into heparinized tubes; the umbilical cords were collected and stored at –80 °C until pharmacological analysis was carried out. The samples were analysed using ultra performance liquid chromatography. Results: The cardiorespiratory parameters of the bitches and of the puppies at birth, and the Apgar scores did not differ significantly between groups. At T1 both the median maternal methadone plasma concentration and the median methadone umbilical cord concentration were higher in group MET compared to group METEPI ( p  = 0.0018 and p  = 0.004, respectively). The maternal plasma concentration was higher than the concentration in the umbilical cords ( p  = 0.05) in group METEPI but not in group MET ( p  = 0.25). Conclusions and clinical relevance: Epidural methadone (0.1 mg kg –1 ) administered to bitches undergoing caesarean section is associated with lower umbilical cord methadone concentrations as compared with intramuscularly administered methadone at higher dosages (0.3 mg kg –1 ).